Pandangan Bapa-Bapa Gereja mengenai Kristus: Studi Komprehensif tentang Kristologi Patristik dan Perkembangan Sejarahnya - Markus Santoso (Sekolah Tinggi Teologi Bethel Ambon, 2025)
Christology as a major branch of Christian theology has undergone significant development since the time of the Church Fathers. Their thinking not only formed the basis of the doctrine of Christ, but also responded to various emerging theological challenges, such as Arianism, Nestorianism, and Monophysitis. This article aims to comprehensively analyze the views of the Church Fathers, especially Origen, Athanasius, Augustine, and Cyril of Alexandria, in formulating the doctrine of christology. The research method used is a qualitative approach with historical, theological, and philosophical analysis of primary and secondary sources. The results show that the Church Fathers have a great contribution to affirming the divinity and humanity of Christ and maintaining the orthodoxy of the church. Concepts such as homoousios and hypostatic unity that they formulated still have relevance in contemporary Christian theological discourse. Their thinking not only became the foundation for church doctrine, but also provided important insights into the challenges of faith and theological differences in the modern world.